2019
DOI: 10.1088/2399-6528/ab3615
|View full text |Cite
|
Sign up to set email alerts
|

Outset of multiple soliton solutions to the nonlinear Schrödinger equation and the coupled Burgers equation

Abstract: The nonlinear Schrödinger equation and the coupled Burgers equation illustrate the status of quantum particles, shock waves, acoustic transmission and traffic flow. Therefore these equations are physically significant in their own right. In this article, the new auxiliary equation method has been contrivanced in order to rummage exact wave solutions to previously stated nonlinear evolution equations (NLEEs). We have developed ample soliton solutions and have to do with the physical importance of the acquired s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…When 2 − 4 < 0 and ≠ 0, Making a comparable study of the found solutions to those existing ever it is claimed that this study ensures the diversity and novelty of our results [32][33][34][35][36][37][38].…”
Section: The Nonlinear Schrodinger Equation Of Fractional Ordermentioning
confidence: 71%
See 2 more Smart Citations
“…When 2 − 4 < 0 and ≠ 0, Making a comparable study of the found solutions to those existing ever it is claimed that this study ensures the diversity and novelty of our results [32][33][34][35][36][37][38].…”
Section: The Nonlinear Schrodinger Equation Of Fractional Ordermentioning
confidence: 71%
“…The solutions of Eq. (2.5) are available in [38]. Now, we formulate the closed form wave solutions of the following space and time fractional nonlinear partial differential equations:…”
Section: Elucidation Of the Proposed Improved Auxiliary Equation Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…In that context, scientists have been solving the problems by explaining those mathematical models through various methods have been exposed to solve the mathematical problems, the solutions from each schemes of which have given various solutions and research on these is ongoing. Among the above methods, very detailed results are found in these two methods namely, improved Bernoulli sub-equation function method (IBSEFM) [22,23] and the new auxiliary equation method (NAEM) [24] which can be further enriched by explaining our research.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore a variety of powerful and modern approaches using computer algebra such as Mathematica or Maple, have recently been developed by several researchers. The available methods are: the auxiliary equation method (Akbar, Ali, & Tanjim, 2019;Akbulut, Kaplan, & Bekir, 2016;Ismail, 2016), the G 0 =G ð Þ-expansion method (Alam, Akbar, & Mohyud-Din, 2014;Bekir & Guner, 2013;Islam & Akbar, 2018a, 2018b, 2018c , the tanh-function method (Ali, 2007), the first integral method (Younis, 2013), the fractional sub-equation method (Alzaidy, 2013), the exp-function method (Zheng, 2013;Yokus, Durur, Ahmad, & Yao, 2020), the modified Kudryashov method (Ege & Misirli, 2014), the variational iteration method (He & Latifizadeh, 2020;Neamaty, Agheli, & Darzi, 2015), the homotopy perturbation method (Ain et al, 2020;Fereidoon, Yaghoobi, & Davoudabadi, 2011;He, 2019aHe, , 2019bYu, He, & Garcia, 2019), the modified simple equation method (Islam & Akbar, 2018c), the Jacobi elliptic method (Zheng & Feng, 2014), the differential transformation method (Rabtah, Erturk, & Momani, 2010), the modified trial equation method (Bulut, Baskonus, & Pandir, 2013), the finite element method (Deng, 2009), the Adomin decomposition method (Dahmani, Mesmoudi, & Bebbouchi, 2008), the Taylor series method , the variational iteration algorithm-I (Ahmad & Khan, 2019;Ahmed, Khan, & Cesarano, 2019) the variational iteration algorithm-II Ahmad, Seadawy, Khan, & Thounthong, 2020), the Riccati transformation method …”
Section: Introductionmentioning
confidence: 99%